Peran Tutor dalam Pembelajaran Program Pendidikan Kesetaraan Paket C di SKB Sidoarjo - Madani, Paige Kharismawati Pramudya; Roesminingsih, Maria Veronica (J+PLUS UNESA, 2023)
Tutors have several important roles in learning, especially in the package C equivalence education program at SKB Sidoarjo. The purpose of this study was to analyze the role of the tutor in learning the UNPK subject in the package C equivalence education program at SKB Sidoarjo and to describe and analyze the supporting and inhibiting factors of tutors in teaching the package C capability program at SKB Sidoarjo. This study used qualitative research methods. The results of the study showed that tutors at the Sidoarjo SKB carried out the role of tutors in learning well. The role of the tutor at SKB Sidoarjo in the most optimal learning is the role of the tutor as informer, director, motivator, facilitator, and evaluator.